Franchisees, change, and the life cycle - Van Tonder, Chris; McMullan, L. (Global Business and Technology Association, 2010)
By virtue of the franchisor-franchisee relationship a franchise is neither a small business nor a large corporateand more aptly viewed as a hybrid organizational form. Despite this anomaly the franchise still has to contendwith the standard business challenges including constant change in the operating context. Mindful of the multiple sources of change that could impact on the franchise, and the paucity of research in this regard, the current study set out to explore the nature of organizational change experienced at the level of the franchise. Twenty-one (21) franchisees of a large retail institution participated in a qualitative study which utilized a semistructuredinterview schedule for data gathering. Franchisee narrative was subjected to content analysis and a multitude of change themes were extracted. The findings revealed that franchises are subjected to an extensive array of changes originating both external and internal to the franchisor. Moreover, it was observed that the salience of change phenomena life cycle stage-specific. The implications of the study are briefly indicated.